2014
DOI: 10.3855/jidc.4637
|View full text |Cite
|
Sign up to set email alerts
|

First report of chronic hepatitis E in renal transplant recipients in Portugal

Abstract: Hepatitis E virus (HEV) infection can be responsible for chronic hepatitis in immunocompromised patients, and can rapidly evolve into fibrosis and/or hepatic cirrhosis. We present two cases of chronic hepatitis E, emphasizing the need to be aware of this entity as a growing etiology of hepatitis in transplant and immunocompromised patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…19 It was interesting to find that the seroprevalence in the Portuguese population was substantial (16.3%), comparing with the fairly low number of autochthonous hepatitis E cases that have been reported so far. 8,20 In fact, most cases of HEV genotype 3 are asymptomatic and the symptomatic ones are not usually recognized because the rate of icteric illness is low and severe hepatitis is rare. 3 However, the high circulation of HEV genotype3 in both domestic pigs 6 and wild boar 21 in Portugal can help explain the substantial seroprevalence in the Portuguese population, which has a strong tradition of pork consumption.…”
Section: Discussionmentioning
confidence: 99%
“…19 It was interesting to find that the seroprevalence in the Portuguese population was substantial (16.3%), comparing with the fairly low number of autochthonous hepatitis E cases that have been reported so far. 8,20 In fact, most cases of HEV genotype 3 are asymptomatic and the symptomatic ones are not usually recognized because the rate of icteric illness is low and severe hepatitis is rare. 3 However, the high circulation of HEV genotype3 in both domestic pigs 6 and wild boar 21 in Portugal can help explain the substantial seroprevalence in the Portuguese population, which has a strong tradition of pork consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Further hospitalized due to a severe acute hepatitis complicated by Guillain-Barré syndrome (L. Santos et al, 2013 ). Also two renal transplant recipients with chronic hepatitis were initially diagnosed with an hepatitis E by the presence of anti-HEV IgM (Breda et al, 2014 ). The screening of 71 archived sera from a Portuguese pediatric cohort (1–13 years old) collected in 1992–1995 found anti-HEV IgG in two children and anti-HEV IgM in one, suggesting that HEV was circulating in the pediatric population of Portugal in the early 1990s (Mesquita et al, 2016b ).…”
Section: Resultsmentioning
confidence: 99%
“…HEV infection is reported to cause chronic hepatitis in 14.1% of solid organ transplant recipients in France [104]. HEV3 was the predominantly genotype reported in HEV infection in HEV-infected solid-organ transplant recipients in France [105], Portugal [106], and Germany [107]. Although HEV3 is not prevalent in South Africa, a case of HEV3 infection in a renal transplant recipient was reported [108].…”
Section: Kidneymentioning
confidence: 99%
“…Patients with chronic HEV are usually reported with persisting high ALT levels and presence of HEV RNA in their serum [106,109]. However, Gerolami et al (2008) revealed a kidney transplant patient with chronic HEV and normal serum ALT concentrations.…”
Section: Kidneymentioning
confidence: 99%